Calidad de servicio al cliente en la Empresa Exclusividades Maye-Naomi de la ciudad de Babahoyo, - Yance Sánchez, Meybeth Naomi (2025)
This study analyzes the quality of customer service at Exclusividades MAYE-NAOMI, identifying major deficiencies in customer care and perception. It was determined that inconsistency in service, long response times, and lack of staff knowledge are factors that negatively impact customer experience. The main objective was to assess customer satisfaction with the provided service, identifying areas for improvement to optimize customer care. The methodology included a descriptive, analytical, and documentary approach, using customer surveys and interviews with the company’s manager. The results revealed that a high percentage of customers believe the service does not meet their expectations, highlighting issues in staff training, efficiency in handling inquiries, and the lack of customer loyalty strategies. Additionally, price perception and the absence of incentives negatively impact customer retention. It is concluded that the company must improve its service protocols, implement training programs for staff, and develop customer loyalty strategies. It is recommended to optimize response times and use digital tools to facilitate more efficient customer communication.